PENERAPAN PENDEKATAN PROBLEM BASED LEARNING TERHADAP PENINGKATAN KEMAMPUAN PENALARAN MATEMATIS SISWA SMA PADA MATERI PELUANG - Ulsan Fitriana (Journal on Education, 2019)
This study aims to improve mathematical reasoning skills in senior high school students Problem based Learning approach to opportunity material. This type of research is classroom action research, which consists of two cycles where each cycle two meetings that go through the stages of planning, implementation, observation and reflection. Data collection techniques used are documentation, observation of teacher and student activities, interviews and tests of mathematical reasoning abilities at the end of each cycle. The subjects of this study were students of class XI - IPS in one of the high schools in Kabupaten Bandung Barat, amounting to 30 people. This research was conducted in odd semester 2018/2019 academic year. The results obtained by the average value of mathematical reasoning of students in the initial test (pretest) was 39.17, in the first cycle increased to 45.83, in the second cycle amounted to 61.00, and at the final test (posttest) of 72.00 . The percentage of completeness of mathematical reasoning of students in the first cycle was 20% and in the second cycle increased to 80%. Based on the results of the study it can be concluded that the Problem based Learning (PBL) approach can improve the mathematical reasoning of the XI-IPS students in one of the high schools in Kabupaten Bandung Barat.